UPAYA PEMBINAAN KELUARGA SAKINAH DAN DAMPAKNYA OLEH LEMBAGA KERAPATAN ADAT NAGARI SALIMPAUNG KABUPATEN TANAH DATAR - Oktavia, Yusi; Zulkifli, Zulkifli; Emrizal, Emrizal; Nofrianti, Mami (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
This research examines the efforts made by the Nagari Traditional Council (KAN) Salimpaung Tanah Datar Regency in fostering the Sakinah family. The problem is the efforts made by the Nagari Traditional Meeting Institution (KAN) Salimpaung, Tanah Datar Regency in fostering the Sakinah family. The purpose of this discussion is to find out and explain what forms of efforts and impacts are caused by the Salimpaung Village Adat (KAN) Kerapatan Adat (KAN) policy, as well as to analyze how Islamic Law reviews the efforts and impacts of the Salimpaung Nagari Traditional Village (KAN) policy in realizing the Sakinah family, Mawaddah, and Rahmah. Data was obtained through interviews and documentation, then the data was narrated descriptively. The results achieved are that KAN Salimpaung has made efforts to create a Sakinah, Mawaddah and Rahmah family. The forms of effort referred to are: (1) Implementation of Pre-Wedding Guidance (Screening) for Prospective Bride and Groom Couples, (2) Making Pre-Marriage Guidance a Requirement for Processing Marriage Permits by Niniak Mamak, and (3) Implementation of Guidance and Coaching Post Wedding. That the efforts to create a Sakinah, Mawaddah and Rahmah family carried out by KAN Salimpaung have an impact, namely: (1) Implementation of Pre-Marital Guidance (Screening) can provide provisions for prospective bride and groom couples to prepare an ideal household (2) Maintaining and strengthening friendship and family relationships (3) Providing an illustration that the provisions of the Salingka Nagari Custom, especially the provisions of the Salimpaung KAN in the field of marriage are in line with the provisions of Islamic law, and (4) Mutually strengthening the Duties and Functions of Religious Counselors in the Office of Religious Affairs (KUA ) with the Duties and Functions of Angku Ampek Pasukuan. Efforts to create a family that is Sakinah, Mawaddah and Rahmah, as has been done by KAN Salimpaung, are in line with the goals of marriage in the Shari'a itself. That Islamic law has noble ideals behind the existing marriage law, namely to create a family that is happy, eternal, peaceful, peaceful and full of love and affection, which are termed Sakinah, Mawaddah and Rahmah, which is basically in line with the aim of carrying out various efforts by KAN Salimpaung.